Preparing Australian diabetes educators for practice: workforce perceptions of the credentialling pathway - Danielle Cooper; Virginia Hagger; Rachel McKeown; Sheri L. Cooper (BMC Medical Education)
Abstract The Australian Credentialled Diabetes Educator (CDE) registered trademark signifies quality care and education to those with diabetes. A review of the Australian Diabetes Educators Association (ADEA) CDE pathway was undertaken to ensure the quality of the CDE credential. The purpose of this study was to examine perceptions of the diabetes education workforce on the current pathway for educating and qualifying CDEs for practice. Stakeholders (e.g. CDEs, students, supervisors, course coordinators) were invited via the ADEA email, e-newsletter and Facebook to complete a 34-item online survey exploring their perceptions of the pathway, focusing on the requisite graduate certificate and subsequent credentialling requirements. Most (80%) of the 319 respondents were CDEs, 15% were CDEs in training and 12% were supervisors or employers. Half of participants (46%) indicated that graduate certificate course alumni were somewhat or very unprepared to take on the role of a diabetes educator (DE) prior to undertaking credentialling to become a CDE. Seventy-one percent of participants indicated more, and a greater variety, of clinical experiences are necessary within the course. Participants recommended formal assessment of competence within the clinical setting. Fifty-four percent of participants disagreed or were unsure that the subsequent credentialling pathway equips CDEs well for practice, indicating it is too onerous, and supported a more streamlined pathway. Findings highlight the need for education and skills-based training beyond the graduate certificate, and assessment of competence in conducting core diabetes skills to better equip CDEs for their role.